The effectiveness of therapeutic strategies for patients with radiculopathy: A network meta-analysis. Issue 1 (April 2018) - Zhang, Xiaoyu; Zhang, Zhiqiang; Wen, Jianzhong; Lu, Jie; Sun, Yingchun; Sang, Dechun
Objectives: The aim of this network meta-analysis is to assess the effectiveness of therapeutic strategies for patients with radiculopathy, including physical, medical, surgical, and other therapies. Methods: We electronically searched electronic databases including PubMed and Embase for randomized controlled trials. The response rate and visual analog scale of pain change were considered as primary outcomes. The outcomes were measured by odds ratio (OR) value and corresponding 95% credible intervals (CrIs) or standardized mean difference (MD) with 95% CrIs. Besides, surface under cumulative ranking curve (SUCRA) were performed to rank efficacy and safety of treatments on each end points. Results: A total of 16 eligible studies with 1071 subjects were included in this analysis. Our results showed that corticosteroid was significantly more effective than control regarding the response rate (OR = 3.86, 95% CrI: 1.16, 12.55). Surgery had a better performance in pain change compared with control (MD = −1.92, 95% CrI: −3.58, −0.15). According to the SUCRA results, corticosteroid, collar, and physiotherapy ranked the highest concerning response rate (SUCRA = 0.656, 0.652, and 0.610, respectively). Surgery, traction, and corticosteroid were superior to others in pain change (SUCRA = 0.866, 0.748, and 0.589, respectively). Conclusion: According to the network meta-analysis result, we recommended surgery as the optimal treatment for radiculopathy patients; traction and corticosteroids were also recommended for their beneficial interventions.